Pamodzi Investment Holdings ; to list or not to list? - Beswick, Claire; Ncube, Mthuli, 1963- ([London] : SAGE, 2016)
In January 2008, the black-owned Pamodzi Investment Holdings (PIH) was at a crossroads, as its chief executive officer (CEO), Ndaba Ntsele, sat down with his board to discuss how to finance the growth of the business. Ntsele and co-director, Solly Sithole, had founded PIH's predecessor, Pamodzi Property Developers, and grown it from nothing in 1979 to a multi-million rand concern, using only debt finance and working capital. PIH, founded in 1997 to take advantage of the opportunities presented by black economic empowerment (BEE) deals, had followed the same funding strategy. This case study examines this topic.
Originally Published in: Beswick, C., & Ncube, M. (2009). Pamodzi Investment Holdings: To List or Not to List? WBS-2009-14. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Padmodzi Investment Holdings (Firm); Business enterprises -- Finance -- Case studies; Strategic planning -- Case studies